1987
DOI: 10.1139/m87-064
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of iron-reducing Alteromonas putrefaciens strains from oil field fluids

Abstract: Gram-negative, aerobic bacteria capable of facultative growth using ferric ions or thiosulfate or sulfite as electron acceptors were readily isolated from oil field fluids. Morphological and biochemical data are presented which support the classification of these isolates as being strains of Alteromonas putrefaciens (mol% G + C in the range 42–56%). The isolates expressed a range of halotolerance and temperature tolerance as some would grow in the presence of 7.5% NaCl and some grew well at 4 °C. These physiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
102
0
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(105 citation statements)
references
References 21 publications
2
102
0
1
Order By: Relevance
“…Fe(III)-and Mn(IV)-reducing microorganisms have been enumerated and cultured on a wide variety of solid, semisolid, and liquid media that are similar in composition to those used for other heterotrophic microorganisms but with the modification that some form of Fe(III) or Mn(IV) was included in the medium. Naturally occurring Fe(III) or Mn(IV) oxides have been employed, as have hematite, goethite, lepidocrocite, synthetic poorly crystalline Fe(III) oxides, FePO4, FeCl3, and Fe(III) citrate (17,45,91,116,155,172,198,236,246,256,282,285,318). For agar media, the Fe(III) or Mn(IV) may be added as an overlay (89,230).…”
Section: Enumeration and Culturing Of Fe(hi) And Mn(iv) Reducersmentioning
confidence: 99%
See 1 more Smart Citation
“…Fe(III)-and Mn(IV)-reducing microorganisms have been enumerated and cultured on a wide variety of solid, semisolid, and liquid media that are similar in composition to those used for other heterotrophic microorganisms but with the modification that some form of Fe(III) or Mn(IV) was included in the medium. Naturally occurring Fe(III) or Mn(IV) oxides have been employed, as have hematite, goethite, lepidocrocite, synthetic poorly crystalline Fe(III) oxides, FePO4, FeCl3, and Fe(III) citrate (17,45,91,116,155,172,198,236,246,256,282,285,318). For agar media, the Fe(III) or Mn(IV) may be added as an overlay (89,230).…”
Section: Enumeration and Culturing Of Fe(hi) And Mn(iv) Reducersmentioning
confidence: 99%
“…This technique may be inappropriate for monitoring Fe(III) reduction in mixed cultures in media which contain significant quantities of sulfate, because sulfate reduction could lead to the formation of black iron sulfides, some of which are magnetic. In liquid medium with Fe(III)-citrate as the electron acceptor, the medium changes from orange-brown to green as Fe(III) is reduced (198,282). At the completion of Fe(III) reduction, the medium typically clears because the Fe(II) forms vivianite [Fe3(PO4)2 -8H20], a white precipitate (201).…”
Section: Enumeration and Culturing Of Fe(hi) And Mn(iv) Reducersmentioning
confidence: 99%
“…shewanella.org). Some Shewanella strains are also able to degrade pollutants such as chlorinated solvents (Petrovskis et al, 1994), petroleum (Semple & Westlake, 1987) and RDX (1,3,5-trinitroperhydro-1,3,5-triazine) (Zhao et al, 2004), some can produce polyunsaturated fatty acids (Bowman et al, 1997;Russell & Nichols, 1999;Satomi et al, 2003) and some are able to grow under extreme conditions (Bozal et al, 2002;Kato et al, 1998;Nogi et al, 1998;Stapleton et al, 2005).…”
mentioning
confidence: 99%
“…It can thus be concluded on the basis of moderate 16s rDNA and DNA-DNA similarity values that strain SB2BT represents a novel species within the genus Shewanella. Though many Shewanella isolates share common phenotypic traits, the 16s rDNA (Fonnesbech-Vogel et al, 1997) and DNA-DNA hybridization studies (Owen et al, 1978;Semple & Westlake, 1987) have revealed the obvious heterogeneity of various strains that have been grouped within the S. putrefaciens group. This paper also supports the fact that without nucleotide sequence analysis, strain SB2BT would have been placed within S. putrefaciens.…”
mentioning
confidence: 99%